TEYL IN INDONESIAN ELEMENTARY SCHOOLS: WHY, WHO, WHAT, AND HOW? (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
English has been eliminated as a compulsory subject in elementary school and replaced with an extracurricular (2013 Curriculum) and elective subject (Merdeka Curriculum). This study is to investigate the Teaching English to Young Learners (TEYL) in elementary schools. An online survey was randomly distributed and responded by 112 teachers from 74 schools in 13 districts (in 5 provinces in Indonesia). The study's samples included 94 English teachers from 66 schools. The questionnaire was designed by providing both closed-response and open-response questions. The data from closed-ended questions was quantitatively examined to determine percentages and frequencies. The data from open-response questions, on the other hand, were investigated qualitatively through data reduction, data display, and conclusion drawing and verification. Despite the pros and cons of the newest curricula, most schools (89% of 74) teach English to students. It was because English is vital for futures; students need to be taught English early; and ensuring that school is not left behind others. Homeroom teachers (61%), specialized English teachers (32%), and English teachers with no relevant educational background (7%) are among those who teach English. The top three teaching topics were vocabulary, grammar, and writing, as stated by 64 teachers (68%), 15 teachers (16%), and 7 teachers (7%), respectively. "Song" was voted 68 times to be used in English class, "Games" was chosen 60 times, "Lecture" was elected 57 times, and "Dialogue/Conversation" received the fewest votes (12 times). TEYL in elementary schools should consider not only the fixed curriculum but also the teachers’ preparedness.